Training Effectiveness Evaluation (TEE) of the Advanced Fire Fighting Training System. Focus on the Trained Person / Curtis C. Cordell and Others. - Cordell, Curtis C. (Distributed by ERIC Clearinghouse, 1983)
A training effectiveness evaluation of the Navy Advanced Fire Fighting Training System was conducted. This system incorporates simulated fires as well as curriculum materials and instruction. The fires are non-pollutant, computer controlled, and installed in a simulated shipboard environment. Two teams of 15 to 16 persons, with varying amounts of fire-fighting experience, were involved in the evaluation. Both performance and knowledge testing were used and a student attitude questionnaire was administered. In addition, specific observations were made of the components of the overall training system. It was determined that the training device provides effective training for fire fighting. Recommendations for modifications in the system and the supporting components were made following the evaluation. (KC)